Cold War Order and Technology Development in Indonesia - Frial Ramadhan Supratman (UIN Sunan Gunung Djati Bandung, 2022)
After revolution period (1949-1950), Indonesians had to face several social and economic problem, urging development in all sectors of life. They needed to build public transportation, communication, education, health and agriculture, emphasizing on “developmentalism” in modernizing society. Meanwhile, Indonesia and other Third World countries also urged decolonization through anti-Westernism and anti-Imperialism. Relations between decolonization and development opened a new discourse in Third World countries in 1950’s. Constructivism approach in political science and international relations emphasize excessively on military and ideological conflicts among liberalism and communism. However, the studies ignore pragmatic view of Third World countries during Cold War in order to develop the countries in economic and social lives. Author finds that Cold War Order forced Third World countries to adapt with anti-imperialism ideology and development necessities. Third World leaders, such as Sukarno, Nehru, Nasser, did not always view Cold War from political rivalry perspective. They urged Third World countries to be strong and advance country through development of new technology. In 1959 Indonesia, for instance, established Bandung Institute of Technology (ITB) in order to produce future Indonesian engineers and scientists. Sukarno also built Planetarium and Observatorium in order to encourage research on astronomy science. Cold War Order which rose after 1940’s offered opportunities for building technology. Indonesia and other Third World countries received many opportunities from Great Powers in building science and technology. In this article, author observes another story of Cold War which not only emphasizes on political and military conflict, but “cooperation” and “development” in building science and technology. Author argues that Cold War Order was not solely shape political conflict among Great Powers in Third World countries, yet it offered opportunities for Indonesia to develop technology.